THE RELATIONSHIP OF HEALTHY LIFESTYLE INDEX (HLI) TO THE OCCURRENCE OF HYPERTENSION IN MOUNTAINS, COASTAL AND URBAN COMMUNITIES - Iis Noventi; Yanis Kartini (LPPM Politeknik Kesehatan Kerta Cendekia, 2019)
Background: Epidemiological transitions cause changes in disease trends from transmitted diseases to non-communicable diseases. One disease that continues to increase in prevalence and have a high-risk complication, namely hypertension. This disease has key risk factor namely lifestyle. The role of lifestyle on the incidence of hypertension is very close, especially in the community city. Surabaya has the highest prevalence of hypertension in Indonesia but has a prevalence and the role of lifestyle to the coastal and mountainous regions has not been studied so has not it is known whether hypertension is only concentrated in urban areas or also has an impact for coastal and mountainous regions. Objective: The purpose of this study was to examine relationship between the Healthy Lifestyle Index score to the occurrence of hypertension in mountainous, coastal, and urban communities. Method: This study was a cross sectional observational study. The samples in this study were 30 people in the coastal community, 30 people in the mountain community and 30 people in the urban community. All of respondents visiting the Supporting Public Health Center of Gili Ketapang, Supporting Public Health Center of Wonotoro, and Public Health Center of Kebonsari. Lifestyle assessment use the Tube version of Healthy Lifestyle Index (HLI) (2015) which consists of domains quality of the diet, physical activity, smoking behavior, and BMI. Data analysis uses statistical tests chi square test to determine the relationship HLI scores with the incidence of hypertension. Result: The relationship of HLI scores with the incidence of hypertension in mountainous communities, hypertension caused by smoking, while hypertension in coastal communities is caused because of eating patterns and lack of activity, hypertension in urban communities is caused due to unhealthy eating patterns, smoking, lack of activity and obesity. Conclusion: There is a significant relationship between the Healthy Lifestyle Index score with the incidence of hypertension in mountainous, coastal and urban areas. Key words: Lifestyle, Hypertension, Mountains, Urban, Coastal.